Assessing the end-organ in peripheral arterial occlusive disease—from contrast—enhanced ultrasound to blood-oxygen-level-dependent MR imaging - Aschwanden, Markus; Partovi, Sasan; Jacobi, Bjoern; Fergus, Nathan; Schulte, Anja-Carina; Robbin, Mark R.; Bilecen, Deniz; Staub, Daniel (Cardiovascular Diagnosis and Therapy, 2014)
Peripheral arterial occlusive disease (PAOD) is a result of atherosclerotic disease which is currently the leading cause of morbidity and mortality in the Western world.Patients with PAOD may present with intermittent claudication or symptoms related to critical limb ischemia. PAOD is associated with increased mortality rates. Stenoses and occlusions are usually detected by macrovascular imaging, including ultrasound and cross-sectional methods. From a pathophysiological view these stenoses and occlusions are affecting the microperfusion in the functional end-organs, such as the skin and skeletal muscle. In the clinical arena new imaging technologies enable the evaluation of the microvasculature. Two technologies currently under investigation for this purpose on the end-organ level in PAOD patients are contrast-enhanced ultrasound (CEUS) and blood-oxygen-level-dependent (BOLD) MR imaging (MRI). The following article is providing an overview about these evolving techniques with a specific focus on skeletal muscle microvasculature imaging in PAOD patients.